2017 WONOEP appraisal: Studying epilepsy as a network disease using systems biology approaches - Mahoney, John M.; Mills, James D.; Muhlebner, Angelika; Noebels, Jeffrey; Potschka, Heidrun; Simonato, Michele; Kobow, Katja (Epilepsia, 2019)
The revolution in high-throughput omics technologies has dramatically expanded our understanding of the epilepsies as complex diseases. It is now clear that further progress in treating the full spectrum of seizure disorders requires a systems-level framework for analyzing and integrating data from multiple omics technologies that moves beyond the search for single molecular alterations to an understanding of dysregulated pathways in epilepsy. Taking such a pathway-centered view requires further integrating the tools of systems biology into epilepsy research. In this appraisal, we highlight and summarize systems biology approaches in basic epilepsy studies as they were discussed during the 2017 Workshop on the Neurobiology of Epilepsy (WONOEP). During the 3-day event, participants exchanged emerging results and thoughts on developing the systems biology of epilepsy, and the promise and limitations of these approaches for the near term.
CRIS-Team Scopus Importer:2019-05-28
Keywords: epigenomics; epilepsy; genomics; proteomics; systems biology

A comprehensive clinico-pathological and genetic evaluation of bottom-of-sulcus focal cortical dysplasia in patients with difficult-to-localize focal epilepsy - Ying, Zhong; Wang, Irene; Blümcke, Ingmar; Bulacio, Juan; Alexopoulos, Andreas; Jehi, Lara; Bingaman, William; Gonzalez-Martinez, Jorge; Kobow, Katja; Niestroj, Lisa Marie; Lal, Dennis; Kölble, Konrad; et al. (Epileptic Disorders, 2019)
Aims. We comprehensively studied the clinical presentation, stereo-EEG and MRI findings, histopathological diagnosis, and brain somatic mutations in a retrospective series of drug-resistant patients with difficult-to-localize epilepsy due to focal cortical dysplasia at the bottom of a sulcus (BOS-FCD).Methods. We identified 10 patients with BOS-FCD from the Cleveland Clinic epilepsy surgery database submitted for intracranial video-EEG monitoring. Brain MRI, including voxel-based morphometric analysis and surgical tissue submitted for histopathology, was reviewed. Paraffin tissue samples from five patients were made available for targeted next-generation sequencing. Postsurgical follow-up was available in nine patients.Results. BOS-FCD was identified in the superior frontal sulcus in six patients, inferior frontal sulcus in one patient, central sulcus in one patient, and intraparietal sulcus in two patients. All patients had stereotyped seizures. Intracranial EEG recordings identified ictal onset at the BOS-FCD in all 10 patients, whereas ictal scalp EEG had a localizing value in only six patients. Complete resection was achieved by lesionectomy or focal corticectomy in nine patients. Histopathologically, six patients had FCD type IIb and three had FCD type IIa. Next-generation sequencing analysis of DNA extracted from lesion-enriched (micro-dissected) tissue from five patients with FCD type II led to the identification of a germline frameshift insertion in DEPDC5, introducing a premature stop in one patient. Eight out of nine patients with available follow-up were completely seizure-free (Engel Class IA) after a mean follow-up period of six years.Conclusion. Our results confirm previous studies classifying difficult-to-localize BOS-FCD into the emerging spectrum of FCD ILAE type II mTORopathies. Further studies with large patient numbers and ultra-deep genetic testing may help to bridge the current knowledge gap in genetic aetiologies of FCD.
CRIS-Team WoS Importer:2019-04-09

Analysis of 1386 epileptogenic brain lesions reveals association with DYRK1A and EGFR - Boßelmann, Christian M.; Leu, Costin; Brünger, Tobias; Hoffmann, Lucas; Baldassari, Sara; Chipaux, Mathilde; Coras, Roland; Kobow, Katja; Hamer, Hajo; Delev, Daniel; Rössler, Karl; Bien, Christian G.; et al. (Nature Communications, 2024)
Lesional focal epilepsy (LFE) is a common and severe seizure disorder caused by epileptogenic lesions, including malformations of cortical development (MCD) and low-grade epilepsy-associated tumors (LEAT). Understanding the genetic etiology of these lesions can inform medical and surgical treatment. We conducted a somatic variant enrichment mega-analysis in brain tissue from 1386 individuals who underwent epilepsy surgery, including 599 previously unpublished individuals with ultra-deep ( > 1600x) targeted panel sequencing. Here we confirm four known associations (BRAF, SLC35A2, MTOR, PTPN11), support eight associations without prior statistical support (FGFR1, PIK3CA, AKT3, NF1, PTEN, RHEB, KRAS, NRAS), and identify novel associations for two genes, DYRK1A and EGFR. Both novel genes show specific histopathological phenotypes, interact with LFE genes and pathways, and may represent promising candidates as biomarkers and potentially druggable target

Assessment of genetic variant burden in epilepsy-associated brain lesions - Niestroj, Lisa Marie; May, Patrick; Artomov, Mykyta; Kobow, Katja; Coras, Roland; Pérez-Palma, Eduardo; Altmüller, Janine; Thiele, Holger; Nürnberg, Peter; Leu, Costin; Palotie, Aarno; Daly, Mark J.; et al. (European journal of human genetics, 2019)
It is challenging to estimate genetic variant burden across different subtypes of epilepsy. Herein, we used a comparative approach to assess the genetic variant burden and genotype–phenotype correlations in four most common brain lesions in patients with drug-resistant focal epilepsy. Targeted sequencing analysis was performed for a panel of 161 genes with a mean coverage of >400×. Lesional tissue was histopathologically reviewed and dissected from hippocampal sclerosis (n = 15), ganglioglioma (n = 16), dysembryoplastic neuroepithelial tumors (n = 8), and focal cortical dysplasia type II (n = 15). Peripheral blood (n = 12) or surgical tissue samples histopathologically classified as lesion-free (n = 42) were available for comparison. Variants were classified as pathogenic or likely pathogenic according to American College of Medical Genetics and Genomics guidelines. Overall, we identified pathogenic and likely pathogenic variants in 25.9% of patients with a mean coverage of 383×. The highest number of pathogenic/likely pathogenic variants was observed in patients with ganglioglioma (43.75%; all somatic) and dysembryoplastic neuroepithelial tumors (37.5%; all somatic), and in 20% of cases with focal cortical dysplasia type II (13.33% somatic, 6.67% germline). Pathogenic/likely pathogenic positive genes were disorder specific and BRAF V600E the only recurrent pathogenic variant. This study represents a reference for the genetic variant burden across the four most common lesion entities in patients with drug-resistant focal epilepsy. The observed large variability in variant burden by epileptic lesion type calls for whole exome sequencing of histopathologically well-characterized tissue in a diagnostic setting and in research to discover novel disease-associated genes.
CRIS-Team Scopus Importer:2019-08-06

Big data in epilepsy: Clinical and research considerations. Report from the Epilepsy Big Data Task Force of the International League Against Epilepsy - Lhatoo, Samden D.; Bernasconi, Neda; Blumcke, Ingmar; Braun, Kees; Buchhalter, Jeffrey; Denaxas, Spiros; Galanopoulou, Aristea; Josephson, Colin; Kobow, Katja; Lowenstein, Daniel; Ryvlin, Philippe; Schulze-Bonhage, Andreas; et al. (Epilepsia, 2020)
Epilepsy is a heterogeneous condition with disparate etiologies and phenotypic and genotypic characteristics. Clinical and research aspects are accordingly varied, ranging from epidemiological to molecular, spanning clinical trials and outcomes, gene and drug discovery, imaging, electroencephalography, pathology, epilepsy surgery, digital technologies, and numerous others. Epilepsy data are collected in the terabytes and petabytes, pushing the limits of current capabilities. Modern computing firepower and advances in machine and deep learning, pioneered in other diseases, open up exciting possibilities for epilepsy too. However, without carefully designed approaches to acquiring, standardizing, curating, and making available such data, there is a risk of failure. Thus, careful construction of relevant ontologies, with intimate stakeholder inputs, provides the requisite scaffolding for more ambitious big data undertakings, such as an epilepsy data commons. In this review, we assess the clinical and research epilepsy landscapes in the big data arena, current challenges, and future directions, and make the case for a systematic approach to epilepsy big data.
CRIS-Team Scopus Importer:2020-08-14
Keywords: big data; epilepsy; epilepsy informatics; epilepsy ontology

Commonalities in epileptogenic processes from different acute brain insults: Do they translate? - Klein, Pavel; Dingledine, Raymond; Aronica, Eleonora; Bernard, Christophe; Blümcke, Ingmar; Boison, Detlev; Brodie, Martin J.; Brooks-Kayal, Amy R.; Engel, Jerome; Forcelli, Patrick A.; Hirsch, Lawrence J.; Kaminski, Rafal M.; et al. (Epilepsia, 2018)
The most common forms of acquired epilepsies arise following acute brain insults such as traumatic brain injury, stroke, or central nervous system infections. Treatment is effective for only 60%-70% of patients and remains symptomatic despite decades of effort to develop epilepsy prevention therapies. Recent preclinical efforts are focused on likely primary drivers of epileptogenesis, namely inflammation, neuron loss, plasticity, and circuit reorganization. This review suggests a path to identify neuronal and molecular targets for clinical testing of specific hypotheses about epileptogenesis and its prevention or modification. Acquired human epilepsies with different etiologies share some features with animal models. We identify these commonalities and discuss their relevance to the development of successful epilepsy prevention or disease modification strategies. Risk factors for developing epilepsy that appear common to multiple acute injury etiologies include intracranial bleeding, disruption of the blood-brain barrier, more severe injury, and early seizures within 1 week of injury. In diverse human epilepsies and animal models, seizures appear to propagate within a limbic or thalamocortical/corticocortical network. Common histopathologic features of epilepsy of diverse and mostly focal origin are microglial activation and astrogliosis, heterotopic neurons in the white matter, loss of neurons, and the presence of inflammatory cellular infiltrates. Astrocytes exhibit smaller K+ conductances and lose gap junction coupling in many animal models as well as in sclerotic hippocampi from temporal lobe epilepsy patients. There is increasing evidence that epilepsy can be prevented or aborted in preclinical animal models of acquired epilepsy by interfering with processes that appear common to multiple acute injury etiologies, for example, in post-status epilepticus models of focal epilepsy by transient treatment with a trkB/PLC?1 inhibitor, isoflurane, or HMGB1 antibodies and by topical administration of adenosine, in the cortical fluid percussion injury model by focal cooling, and in the albumin posttraumatic epilepsy model by losartan. Preclinical studies further highlight the roles of mTOR1 pathways, JAK-STAT3, IL-1R/TLR4 signaling, and other inflammatory pathways in the genesis or modulation of epilepsy after brain injury. The wealth of commonalities, diversity of molecular targets identified preclinically, and likely multidimensional nature of epileptogenesis argue for a combinatorial strategy in prevention therapy. Going forward, the identification of impending epilepsy biomarkers to allow better patient selection, together with better alignment with multisite preclinical trials in animal models, should guide the clinical testing of new hypotheses for epileptogenesis and its prevention.
EVALuna2:7389

Correction to: Ganglioglioma with adverse clinical outcome and atypical histopathological features were defined by alterations in PTPN11/KRAS/NF1 and other RAS-/MAP-Kinase pathway genes (Acta Neuropathologica, (2023), 10.1007/s00401-023-02561-5) - Hoffmann, Lucas; Coras, Roland; Kobow, Katja; López-Rivera, Javier A.; Lal, Dennis; Leu, Costin; Najm, Imad; Nürnberg, Peter; Herms, Jochen; Harter, Patrick N.; Bien, Christian G.; Kalbhenn, Thilo; et al. (Acta Neuropathologica, 2023)
In the original publication, incorrect version of Fig. 3 and wrong format of Table 1 were published. Specifically, the labels in Fig. 3 were missing and columns of Table 1 were not in the right format. The correct versions of Fig. 3 and Table 1 are shown below. The original article has been corrected.
CRIS-Team Scopus Importer:2023-05-05

Correction to: The specific DNA methylation landscape in focal cortical dysplasia ILAE type 3D (Acta Neuropathologica Communications, (2023), 11, 1, (129), 10.1186/s40478-023-01618-6) - Wang, Dan Dan; Katoch, Mitali; Jabari, Samir; Blümcke, Ingmar; Blumenthal, David B.; Lu, De Hong; Coras, Roland; Wang, Yu Jiao; Shi, Jie; Zhou, Wen Jing; Kobow, Katja; Piao, Yue Shan (Acta Neuropathologica Communications, 2024)
Following publication of the original article [1], the authors identified errors in the reference list and citations. Due to a technical error a wrong article version for the references and citations was used. The original article [1] has been corrected.
CRIS-Team Scopus Importer:2024-04-05

Deep histopathology genotype–phenotype analysis of focal cortical dysplasia type II differentiates between the GATOR1-altered autophagocytic subtype IIa and MTOR-altered migration deficient subtype IIb - Honke, Jonas; Hoffmann, Lucas; Coras, Roland; Kobow, Katja; Leu, Costin; Pieper, Tom; Hartlieb, Till; Bien, Christian G.; Woermann, Friedrich; Cloppenborg, Thomas; Kalbhenn, Thilo; Gaballa, Ahmed; et al. (Acta Neuropathologica Communications, 2023)
Focal cortical dysplasia type II (FCDII) is the most common cause of drug-resistant focal epilepsy in children. Herein, we performed a deep histopathology-based genotype–phenotype analysis to further elucidate the clinico-pathological and genetic presentation of FCDIIa compared to FCDIIb. Seventeen individuals with histopathologically confirmed diagnosis of FCD ILAE Type II and a pathogenic variant detected in brain derived DNA whole-exome sequencing or mTOR gene panel sequencing were included in this study. Clinical data were directly available from each contributing centre. Histopathological analyses were performed from formalin-fixed, paraffin-embedded tissue samples using haematoxylin–eosin and immunohistochemistry for NF-SMI32, NeuN, pS6, p62, and vimentin. Ten individuals carried loss-of-function variants in the GATOR1 complex encoding genes DEPDC5 (n = 7) and NPRL3 (n = 3), or gain-of-function variants in MTOR (n = 7). Whereas individuals with GATOR1 variants only presented with FCDIIa, i.e., lack of balloon cells, individuals with MTOR variants presented with both histopathology subtypes, FCDIIa and FCDIIb. Interestingly, 50% of GATOR1-positive cases showed a unique and predominantly vacuolizing phenotype with p62 immunofluorescent aggregates in autophagosomes. All cases with GATOR1 alterations had neurosurgery in the frontal lobe and the majority was confined to the cortical ribbon not affecting the white matter. This pattern was reflected by subtle or negative MRI findings in seven individuals with GATOR1 variants. Nonetheless, all individuals were seizure-free after surgery except four individuals carrying a DEPDC5 variant. We describe a yet underrecognized genotype–phenotype correlation of GATOR1 variants with FCDIIa in the frontal lobe. These lesions were histopathologically characterized by abnormally vacuolizing cells suggestive of an autophagy-altered phenotype. In contrast, individuals with FCDIIb and brain somatic MTOR variants showed larger lesions on MRI including the white matter, suggesting compromised neural cell migration.
CRIS-Team Scopus Importer:2023-11-17

Deep sequencing reveals increased DNA methylation in chronic rat epilepsy - Kobow, Katja; Kaspi, Antony; Harikrishnan, K. N.; Kiese, Katharina; Ziemann, Mark; Khurana, Ishant; Fritzsche, Ina; Hauke, Jan; Hahnen, Eric; Coras, Roland; Muehlebner, Angelika; El-Osta, Assam; et al. (Acta Neuropathologica, 2013)
Epilepsy is a frequent neurological disorder, although onset and progression of seizures remain difficult to predict in affected patients, irrespective of their epileptogenic condition. Previous studies in animal models as well as human epileptic brain tissue revealed a remarkably diverse pattern of gene expression implicating epigenetic changes to contribute to disease progression. Here we mapped for the first time global DNA methylation patterns in chronic epileptic rats and controls. Using methyl-CpG capture associated with massive parallel sequencing (Methyl-Seq) we report the genomic methylation signature of the chronic epileptic state. We observed a predominant increase, rather than loss of DNA methylation in chronic rat epilepsy. Aberrant methylation patterns were inversely correlated with gene expression changes using mRNA sequencing from same animals and tissue specimens. Administration of a ketogenic, high-fat, low-carbohydrate diet attenuated seizure progression and ameliorated DNA methylation mediated changes in gene expression. This is the first report of unsupervised clustering of an epigenetic mark being used in epilepsy research to separate epileptic from non-epileptic animals as well as from animals receiving anti-convulsive dietary treatment. We further discuss the potential impact of epigenetic changes as a pathogenic mechanism of epileptogenesis.
EVALuna2:7211

D-galactose Supplementation for the Treatment of Mild Malformation of Cortical Development with Oligodendroglial Hyperplasia in Epilepsy (MOGHE): A Pilot Trial of Precision Medicine After Epilepsy Surgery - Aledo-Serrano, Ángel; Valls-Carbó, Adrián; Fenger, Christina D.; Groeppel, Gudrun; Hartlieb, Till; Pascual, Irene; Herraez, Erika; Cabal, Borja; García-Morales, Irene; Toledano, Rafael; Budke, Marcelo; Beltran-Corbellini, Álvaro; et al. (Neurotherapeutics, 2023)
MOGHE is defined as mild malformation of cortical development with oligodendroglial hyperplasia in epilepsy. Approximately half of the patients with histopathologically confirmed MOGHE carry a brain somatic variant in the SLC35A2 gene encoding a UDP-galactose transporter. Previous research showed that D-galactose supplementation results in clinical improvement in patients with a congenital disorder of glycosylation due to germline variants in SLC35A2. We aimed to evaluate the effects of D-galactose supplementation in patients with histopathologically confirmed MOGHE, with uncontrolled seizures or cognitive impairment and epileptiform activity at the EEG after epilepsy surgery (NCT04833322). Patients were orally supplemented with D-galactose for 6 months in doses up to 1.5 g/kg/day and monitored for seizure frequency including 24-h video-EEG recording, cognition and behavioral scores, i.e., WISC, BRIEF-2, SNAP-IV, and SCQ, and quality of life measures, before and 6 months after treatment. Global response was defined by > 50% improvement of seizure frequency and/or cognition and behavior (clinical global impression of “much improved” or better). Twelve patients (aged 5–28 years) were included from three different centers. Neurosurgical tissue samples were available in all patients and revealed a brain somatic variant in SLC35A2 in six patients (non-present in the blood). After 6 months of supplementation, D-galactose was well tolerated with just two patients presenting abdominal discomfort, solved after dose spacing or reduction. There was a 50% reduction or higher of seizure frequency in 3/6 patients, with an improvement at EEG in 2/5 patients. One patient became seizure-free. An improvement of cognitive/behavioral features encompassing impulsivity (mean SNAP-IV − 3.19 [− 0.84; − 5.6]), social communication (mean SCQ − 2.08 [− 0.63; − 4.90]), and executive function (BRIEF-2 inhibit − 5.2 [− 1.23; − 9.2]) was observed. Global responder rate was 9/12 (6/6 in SLC35A2-positive). Our results suggest that supplementation with D-galactose in patients with MOGHE is safe and well tolerated and, although the efficacy data warrant larger studies, it might build a rationale for precision medicine after epilepsy surgery.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Developmental and epileptic encephalopathy; Genetic epilepsy; Neurogenetics; SLC35A2; Somatic mutation

DISCOVERY AND PATHOGENICITY ASSESSMENT OF NEUROPATHOLOGY-ASSOCIATED GENE VARIANTS - Neupert, L. -M.; May, P.; Kobow, K.; Nothnagel, M.; Nuernberg, P.; Freiman, T.; Harter, P.; Klein, K. M.; Weber, Y.; Blümcke, Ingmar; Lal, D. (2017)
EVALuna2:7377

DNA methylation-based classification of malformations of cortical development in the human brain - Jabari, Samir; Kobow, Katja; Pieper, Tom; Hartlieb, Till; Kudernatsch, Manfred; Polster, Tilman; Bien, Christian G.; Kalbhenn, Thilo; Simon, Matthias; Hamer, Hajo; Roessler, Karl; Feucht, Martha; et al. (Acta Neuropathologica, 2022)
Malformations of cortical development (MCD) comprise a broad spectrum of structural brain lesions frequently associated with epilepsy. Disease definition and diagnosis remain challenging and are often prone to arbitrary judgment. Molecular classification of histopathological entities may help rationalize the diagnostic process. We present a retrospective, multi-center analysis of genome-wide DNA methylation from human brain specimens obtained from epilepsy surgery using EPIC 850 K BeadChip arrays. A total of 308 samples were included in the study. In the reference cohort, 239 formalin-fixed and paraffin-embedded (FFPE) tissue samples were histopathologically classified as MCD, including 12 major subtype pathologies. They were compared to 15 FFPE samples from surgical non-MCD cortices and 11 FFPE samples from post-mortem non-epilepsy controls. We applied three different statistical approaches to decipher the DNA methylation pattern of histopathological MCD entities, i.e., pairwise comparison, machine learning, and deep learning algorithms. Our deep learning model, which represented a shallow neuronal network, achieved the highest level of accuracy. A test cohort of 43 independent surgical samples from different epilepsy centers was used to test the precision of our DNA methylation-based MCD classifier. All samples from the test cohort were accurately assigned to their disease classes by the algorithm. These data demonstrate DNA methylation-based MCD classification suitability across major histopathological entities amenable to epilepsy surgery and age groups and will help establish an integrated diagnostic classification scheme for epilepsy-associated MCD.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Brain development; Cortical malformation; Deep learning; Epigenetic; Epilepsy

Dynamic Regulation of the Adenosine Kinase Gene during Early Postnatal Brain Development and Maturation - Kiese, Katharina; Jablonski, Janos; Boison, Detlev; Kobow, Katja (Frontiers in Molecular Neuroscience, 2016)
The ubiquitous metabolic intermediary and nucleoside adenosine is a "master regulator" in all living systems. Under baseline conditions adenosine kinase (ADK) is the primary enzyme for the metabolic clearance of adenosine. By regulating the availability of adenosine, ADK is a critical upstream regulator of complex homeostatic and metabolic networks. Not surprisingly, ADK dysfunction is involved in several pathologies, including diabetes, epilepsy, and cancer. ADK protein exists in the two isoforms nuclear ADK-L, and cytoplasmic ADK-S, which are subject to dynamic expression changes during brain development and in response to brain injury; however, gene expression changes of the Adk gene as well as regulatory mechanisms that direct the cell-type and isoform specific expression of ADK have never been investigated. Here we analyzed potential gene regulatory mechanisms that may influence Adk expression including DNA promoter methylation, histone modifications and transcription factor binding. Our data suggest binding of transcription factor SP1 to the Adk promoter influences the regulation of Adk expression.
EVALuna2:7344

Epigenetic control of epilepsy target genes contributes to a cellular memory of epileptogenesis in cultured rat hippocampal neurons - Kiese, Katharina; Jablonski, J.; Hackenbracht, J.; Wrosch, Jana Katharina; Groemer, Teja W.; Kornhuber, Johannes; Blümcke, Ingmar; Kobow, K. (Acta Neuropathologica Communications, 2017)
Hypersynchronous neuronal excitation manifests clinically as seizure (ictogenesis), and may recur spontaneously and repetitively after a variable latency period (epileptogenesis). Despite tremendous research efforts to describe molecular pathways and signatures of epileptogenesis, molecular pathomechanisms leading to chronic epilepsy remain to be clarified. We hypothesized that epigenetic modifications may form the basis for a cellular memory of epileptogenesis, and used a primary neuronal cell culture model of the rat hippocampus to study the translation of massive neuronal excitation into persisting changes of epigenetic signatures and pro-epileptogenic target gene expression. Increased spontaneous activation of cultured neurons was detected 3 and 7 days after stimulation with 10 ?M glutamate when compared to sham-treated time-matched controls using calcium-imaging in vitro. Chromatin-immunoprecipitation experiments revealed short-term (3 h, 7 h, and 24 h) and long-term (3 d and 2 weeks) changes in histone modifications, which were directly linked to decreased expression of two selected epilepsy target genes, e.g. excitatory glutamate receptor genes Gria2 and Grin2a. Increased promoter methylation observed 4 weeks after glutamate stimulation at respective genes suggested long-term repression of Gria2 and Grin2a genes. Inhibition of glutamatergic activation or blocking the propagation of action potentials in cultured neurons rescued altered gene expression and regulatory epigenetic modifications. Our data support the concept of a cellular memory of epileptogenesis and persisting epigenetic modifications of epilepsy target genes, which are able to turn normal into pro-epileptic neurons and circuits.
EVALuna2:7391

Epigenetic genes and epilepsy - emerging mechanisms and clinical applications - Van Loo, Karen M. J.; Carvill, Gemma L.; Becker, Albert J.; Conboy, Karen; Goldman, Alica M.; Kobow, Katja; Lopes-Cendes, Iscia; Reid, Christopher A.; Van Vliet, Erwin A.; Henshall, David C. (Nature Reviews Neurology, 2022)
An increasing number of epilepsies are being attributed to variants in genes with epigenetic functions. The products of these genes include factors that regulate the structure and function of chromatin and the placing, reading and removal of epigenetic marks, as well as other epigenetic processes. In this Review, we provide an overview of the various epigenetic processes, structuring our discussion around five function-based categories: DNA methylation, histone modifications, histone-DNA crosstalk, non-coding RNAs and chromatin remodelling. We provide background information on each category, describing the general mechanism by which each process leads to altered gene expression. We also highlight key clinical and mechanistic aspects, providing examples of genes that strongly associate with epilepsy within each class. We consider the practical applications of these findings, including tissue-based and biofluid-based diagnostics and precision medicine-based treatments. We conclude that variants in epigenetic genes are increasingly found to be causally involved in the epilepsies, with implications for disease mechanisms, treatments and diagnostics.
CRIS-Team WoS Importer:2022-07-29

Epigenetic mechanisms in epilepsy - Kobow, Katja; Blümcke, Ingmar (Progress in Brain Research, 2014)
In humans, genomic DNA is organized in 23 chromosome pairs coding for roughly 25,000 genes. Not all of them are active at all times. During development, a broad range of different cell types needs to be generated in a highly ordered and reproducible manner, requiring selective gene expression programs. Epigenetics can be regarded as the information management system that is able to index or bookmark distinct regions in our genome to regulate the readout of DNA. It further comprises the molecular memory of any given cell, allowing it to store information of previously experienced external (e.g., environmental) or internal (e.g., developmental) stimuli, to learn from this experience and to respond. The underlying epigenetic mechanisms can be synergistic, antagonistic, or mutually exclusive and their large variety combined with the variability and interdependence is thought to provide the molecular basis for any phenotypic variation in physiological and pathological conditions. Thus, widespread reconfiguration of the epigenome is not only a key feature of neurodevelopment, brain maturation, and adult brain function but also disease.
EVALuna2:7267

Epigenetics and Epilepsy - Henshall, David C.; Kobow, Katja (Cold Spring Harbor Perspectives in Medicine, 2015)
Epigenetic processes in the brain involve the transfer of information arising from short-lived cellular signals and changes in neuronal activity into lasting effects on gene expression. Key molecular mediators of epigenetics include methylation of DNA, histone modifications, and noncoding RNAs. Emerging findings in animal models and human brain tissue reveal that epilepsy and epileptogenesis are associated with changes to each of these contributors to the epigenome. Understanding and influencing the molecular mechanisms controlling epigenetic change could open new avenues for treatment. DNA methylation, particularly hypermethylation, has been found to increase within gene body regions and interference with DNA methylation in epilepsy can change gene expression profiles and influence epileptogenesis. Posttranscriptional modification of histones, including transient as well as sustained changes to phosphorylation and acetylation, have been reported, which appear to influence gene expression. Finally, roles have emerged for noncoding RNAs in brain excitability and seizure thresholds, including microRNA and long noncoding RNA. Together, research supports strong effects of epigenetics influencing gene expression in epilepsy, suggesting future therapeutic approaches to manipulate epigenetic processes to treat or prevent epilepsy.
EVALuna2:7309

Epigenetics in epilepsy - Kobow, K.; Blümcke, Ingmar (Neuroscience Letters, 2018)
Approximately 50 million people have epilepsy, making it the most common chronic and severe neurological disease worldwide, with increased risk of mortality and psychological and socioeconomic consequences impairing quality of life. More than 30% of patients with epilepsy have inadequate control of their seizures with drug therapy. Any structural brain lesion can provoke epilepsy. However, progression of seizure activity as well as the development of drug-resistance remains difficult to predict, irrespective of the underlying epileptogenic condition, i.e., traumatic brain injury, developmental brain lesions, brain tumors or genetic inheritance. Mutated DNA sequences in genes encoding for ion channels or neurotransmitter receptors have been identified in hereditary focal or generalized epilepsies, but genotype-phenotype correlations are poor, arguing for additional factors determining the effect of a genetic predisposition. The dynamics of epigenetic mechanisms (e.g. DNA methylation, histone modifications, chromatin remodelling, and non-coding RNAs) provide likely explanations for common features in epilepsy and other complex diseases, including late onset, parent-of-origin effects, discordance of monozygotic twins, and fluctuation of symptoms. In addition, many focal epilepsies, including focal cortical dysplasias (FCDs), glio-neuronal tumors (e.g. ganglioglioma), or temporal lobe epilepsy with hippocampal sclerosis (TLE-HS), do not seem to primarily associate with hereditary traits, suggesting other pathogenic mechanisms. Herein we will discuss the many faces of the epigenetic machinery, which provides powerful tools and mechanisms to propagate epileptogenicity and likely also contribute to the epileptogenic memory in chronic and difficult-to-treat epilepsies.
EVALuna2:34596

Etiology matters - Genomic DNA Methylation Patterns in Three Rat Models of Acquired Epilepsy - Debski, Konrad J.; Pitkanen, Asla; Puhakka, Noora; Bot, Anna M.; Khurana, Ishant; Harikrishnan, K. N.; Ziemann, Mark; Kaspi, Antony; El-Osta, Assam; Lukasiuk, Katarzyna; Kobow, Katja (Scientific Reports, 2016)
This study tested the hypothesis that acquired epileptogenesis is accompanied by DNA methylation changes independent of etiology. We investigated DNA methylation and gene expression in the hippocampal CA3/dentate gyrus fields at 3 months following epileptogenic injury in three experimental models of epilepsy: focal amygdala stimulation, systemic pilocarpine injection, or lateral fluid-percussion induced traumatic brain injury (TBI) in rats. In the models studies, DNA methylation and gene expression profiles distinguished controls from injured animals. We observed consistent increased methylation in gene bodies and hypomethylation at non-genic regions. We did not find a common methylation signature in all three different models and few regions common to any two models. Our data provide evidence that genome-wide alteration of DNA methylation signatures is a general pathomechanism associated with epileptogenesis and epilepsy in experimental animal models, but the broad pathophysiological differences between models (i.e. pilocarpine, amygdala stimulation, and post-TBI) are reflected in distinct etiology-dependent DNA methylation patterns.
EVALuna2:7321

Experimental epileptogenesis in a cell culture model of primary neurons from rat brain: A temporal multi‐scale study - Jablonski, Janos; Hoffmann, Lucas; Blümcke, Ingmar; Fejtová, Anna; Uebe, Steffen; Ekici, Arif Bülent; Gnatkovsky, Vadym; Kobow, Katja (Cells, 2021)
Understanding seizure development requires an integrated knowledge of different scales of organization of epileptic networks. We developed a model of “epilepsy‐in‐a‐dish” based on dissociated primary neuronal cells from neonatal rat hippocampus. We demonstrate how a single application of glutamate stimulated neurons to generate spontaneous synchronous spiking activity with further progression into spontaneous seizure‐like events after a distinct latency period. By computational analysis, we compared the observed neuronal activity in vitro with intracranial electroencephalography (EEG) data recorded from epilepsy patients and identified strong similarities, including a related sequence of events with defined onset, progression, and termination. Next, a link between the neurophysiological changes with network composition and cellular structure down to molecular changes was established. Temporal development of epileptiform network activity correlated with increased neurite outgrowth and altered branching, increased ratio of glutamatergic over GABAergic synapses, and loss of calbindin‐positive interneurons, as well as genome‐wide alterations in DNA methylation. Differentially methylated genes were engaged in various cellular activities related to cellular structure, intracellular signaling, and regulation of gene expression. Our data provide evidence that a single short‐term excess of glutamate is sufficient to induce a cascade of events covering different scales from molecule‐ to network‐level, all of which jointly contribute to seizure development.
CRIS-Team Scopus Importer:2021-11-12
Keywords: DNA methylation; Epigenetic; Epilepsy; In vitro

Finding a better drug for epilepsy: Antiepileptogenesis targets - Kobow, Katja; Kobow, Katja; Auvin, Stephane; Jensen, Frances; Loescher, Wolfgang; Mody, Istvan; Potschka, Heidrun; Prince, David; Sierra, Alejandra; Simonato, Michele; Pitkaenen, Asla; Nehlig, Astrid; et al. (Epilepsia, 2012)
For several decades, both in vitro and in vivo models of seizures and epilepsy have been employed to unravel the molecular and cellular mechanisms underlying the occurrence of spontaneous recurrent seizures (SRS)the defining hallmark of the epileptic brain. However, despite great advances in our understanding of seizure genesis, investigators have yet to develop reliable biomarkers and surrogate markers of the epileptogenic process. Sadly, the pathogenic mechanisms that produce the epileptic condition, especially after precipitating events such as head trauma, inflammation, or prolonged febrile convulsions, are poorly understood. A major challenge has been the inherent complexity and heterogeneity of known epileptic syndromes and the differential genetic susceptibilities exhibited by patients at risk. Therefore, it is unlikely that there is only one fundamental pathophysiologic mechanism shared by all the epilepsies. Identification of antiepileptogenesis targets has been an overarching goal over the last decade, as current anticonvulsant medications appear to influence only the acute process of ictogenesis. Clearly, there is an urgent need to develop novel therapeutic interventions that are disease modifyingtherapies that either completely or partially prevent the emergence of SRS. An important secondary goal is to develop new treatments that can also lessen the burden of epilepsy comorbidities (e.g., cognitive impairment, mood disorders) by preventing or reducing the deleterious changes during the epileptogenic process. This review summarizes novel antiepileptogenesis targets that were critically discussed at the XIth Workshop on the Neurobiology of Epilepsy (WONOEP XI) meeting in Grottaferrata, Italy. Further, emerging neurometabolic links among several target mechanisms and highlights of the panel discussion are presented.
Keywords: Epileptogenesis; Neuroprotection; Antiepileptic drug; Ion channel; Epigenetics; Neurotrophic factors; Metabolism; Biomarker; Ketogenic diet

Frequent SLC35A2 brain mosaicism in mild malformation of cortical development with oligodendroglial hyperplasia in epilepsy (MOGHE) - Bonduelle, Thomas; Hartlieb, Till; Baldassari, Sara; Sim, Nam Suk; Kim, Se Hoon; Kang, Hoon Chul; Kobow, Katja; Coras, Roland; Chipaux, Mathilde; Dorfmüller, Georg; Adle-Biassette, Homa; Aronica, Eleonora; et al. (Acta Neuropathologica Communications, 2021)
Focal malformations of cortical development (MCD) are linked to somatic brain mutations occurring during neurodevelopment. Mild malformation of cortical development with oligodendroglial hyperplasia in epilepsy (MOGHE) is a newly recognized clinico-pathological entity associated with pediatric drug-resistant focal epilepsy, and amenable to neurosurgical treatment. MOGHE is histopathologically characterized by clusters of increased oligodendroglial cell densities, patchy zones of hypomyelination, and heterotopic neurons in the white matter. The molecular etiology of MOGHE remained unknown so far. We hypothesized a contribution of mosaic brain variants and performed deep targeted gene sequencing on 20 surgical MOGHE brain samples from a single-center cohort of pediatric patients. We identified somatic pathogenic SLC35A2 variants in 9/20 (45%) patients with mosaic rates ranging from 7 to 52%. SLC35A2 encodes a UDP-galactose transporter, previously implicated in other malformations of cortical development (MCD) and a rare type of congenital disorder of glycosylation. To further clarify the histological features of SLC35A2-brain tissues, we then collected 17 samples with pathogenic SLC35A2 variants from a multicenter cohort of MCD cases. Histopathological reassessment including anti-Olig2 staining confirmed a MOGHE diagnosis in all cases. Analysis by droplet digital PCR of pools of microdissected cells from one MOGHE tissue revealed a variant enrichment in clustered oligodendroglial cells and heterotopic neurons. Through an international consortium, we assembled an unprecedented series of 26 SLC35A2-MOGHE cases providing evidence that mosaic SLC35A2 variants, likely occurred in a neuroglial progenitor cell during brain development, are a genetic marker for MOGHE.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Brain mosaicism; Epilepsy; Focal cortical dysplasia; Glycosylation; Malformations of cortical development; SLC35A2 gene

Ganglioglioma with adverse clinical outcome and atypical histopathological features were defined by alterations in PTPN11/KRAS/NF1 and other RAS-/MAP-Kinase pathway genes - Hoffmann, Lucas; Coras, Roland; Kobow, Katja; López-Rivera, Javier A.; Lal, Dennis; Leu, Costin; Najm, Imad; Nürnberg, Peter; Herms, Jochen; Harter, Patrick N.; Bien, Christian G.; Kalbhenn, Thilo; et al. (Acta Neuropathologica, 2023)
Exome-wide sequencing studies recently described PTPN11 as a novel brain somatic epilepsy gene. In contrast, germline mutations of PTPN11 are known to cause Noonan syndrome, a multisystem disorder characterized by abnormal facial features, developmental delay, and sporadically, also brain tumors. Herein, we performed a deep phenotype-genotype analysis of a comprehensive series of ganglioglioma (GG) with brain somatic alterations of the PTPN11/KRAS/NF1 genes compared to GG with common MAP-Kinase signaling pathway alterations, i.e., BRAFV600E. Seventy-two GG were submitted to whole exome sequencing and genotyping and 84 low grade epilepsy associated tumors (LEAT) to DNA-methylation analysis. In 28 tumours, both analyses were available from the same sample. Clinical data were retrieved from hospital files including disease onset, age at surgery, brain localization, and seizure outcome. A comprehensive histopathology staining panel was available in all cases. We identified eight GG with PTPN11 alterations, copy number variant (CNV) gains of chromosome 12, and the commonality of additional CNV gains in NF1, KRAS, FGFR4 and RHEB, as well as BRAFV600E alterations. Histopathology revealed an atypical glio-neuronal phenotype with subarachnoidal tumor spread and large, pleomorphic, and multinuclear cellular features. Only three out of eight patients with GG and PTPN11/KRAS/NF1 alterations were free of disabling-seizures 2 years after surgery (38% had Engel I). This was remarkably different from our series of GG with only BRAFV600E mutations (85% had Engel I). Unsupervised cluster analysis of DNA methylation arrays separated these tumours from well-established LEAT categories. Our data point to a subgroup of GG with cellular atypia in glial and neuronal cell components, adverse postsurgical outcome, and genetically characterized by complex alterations in PTPN11 and other RAS-/MAP-Kinase and/or mTOR signaling pathways. These findings need prospective validation in clinical practice as they argue for an adaptation of the WHO grading system in developmental, glio-neuronal tumors associated with early onset focal epilepsy.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Brain; DNA methylation; Epilepsy; Seizure; Summary plots

Genomic DNA methylation distinguishes subtypes of human focal cortical dysplasia - Kobow, Katja; Ziemann, Mark; Kaipananickal, Harikrishnan; Khurana, Ishant; Mühlebner, Angelika; Feucht, Martha; Hainfellner, Johannes A.; Czech, Thomas; Aronica, Eleonora; Pieper, Tom; Holthausen, Hans; Kudernatsch, Manfred; et al. (Epilepsia, 2019)
Objectives: Focal cortical dysplasia (FCD) is a major cause of drug-resistant focal epilepsy in children, and the clinicopathological classification remains a challenging issue in daily practice. With the recent progress in DNA methylation–based classification of human brain tumors we examined whether genomic DNA methylation and gene expression analysis can be used to also distinguish human FCD subtypes. Methods: DNA methylomes and transcriptomes were generated from massive parallel sequencing in 15 surgical FCD specimens, matched with 5 epilepsy and 6 nonepilepsy controls. Results: Differential hierarchical cluster analysis of DNA methylation distinguished major FCD subtypes (ie, Ia, IIa, and IIb) from patients with temporal lobe epilepsy patients and nonepileptic controls. Targeted panel sequencing identified a novel likely pathogenic variant in DEPDC5 in a patient with FCD type IIa. However, no enrichment of differential DNA methylation or gene expression was observed in mechanistic target of rapamycin (mTOR) pathway–related genes. Significance: Our studies extend the evidence for disease-specific methylation signatures toward focal epilepsies in favor of an integrated clinicopathologic and molecular classification system of FCD subtypes incorporating genomic methylation.
CRIS-Team Scopus Importer:2019-06-18
Keywords: diagnostic biomarker; epigenetic; focal cortical dysplasia; focal epilepsy; mTOR pathway

Glucocorticoid modulation of synaptic plasticity in the human temporal cortex of epilepsy patients: Does chronic stress contribute to memory impairment? - Brandner, Sebastian; Schröter, Sarah; Çalışkan, Gürsel; Salar, Seda; Kobow, Katja; Coras, Roland; Blümcke, Ingmar; Hamer, Hajo; Schwarz, Michael; Buchfelder, Michael; Maslarova, Anna (Epilepsia, 2021)
Objective: Memory impairment is common in patients with temporal lobe epilepsy and seriously affects life quality. Chronic stress is a recognized cofactor in epilepsy and can also impair memory function. Furthermore, increased cortisol levels have been reported in epilepsy patients. Animal models have suggested that aggravating effects of stress on memory and synaptic plasticity were mediated via glucocorticoids. The aim of this study was, therefore, to investigate the effect of glucocorticoid receptor (GR) modulation on synaptic plasticity in the human cortex of epilepsy patients. Methods: We performed field potential recordings in acute slices from the temporal neocortex of patients who underwent surgery for drug-resistant temporal lobe epilepsy. Synaptic plasticity was investigated by a theta-burst stimulation (TBS) protocol for induction of long-term potentiation (LTP) in the presence of GR modulators. Results: LTP was impaired in temporal cortex from epilepsy patients. Pretreatment of the slices with the GR antagonist mifepristone (RU486) improved LTP induction, suggesting that LTP impairment was due to baseline GR activation in the human cortex. The highly potent GR agonist dexamethasone additionally weakened synaptic strength in an activity-dependent manner when applied after TBS. Significance: Our results show a direct negative glucocorticoid effect on synaptic potentiation in the human cortex and imply chronic activation of GRs. Chronic stress may therefore contribute to memory impairment in patients with temporal lobe epilepsy. Furthermore, the activity-dependent acute inhibitory effect of dexamethasone suggests a mechanism of synaptic downscaling by which postictally increased cortisol levels may prevent pathologic plasticity upon seizures.
CRIS-Team Scopus Importer:2021-10-29
Keywords: dexamethasone; epilepsy; human cortex; long-term potentiation; stress

Guidelines for the use of flow cytometry and cell sorting in immunological studies (second edition) - Cossarizza, Andrea; Acs, Andreas; Adam, Dieter; Adam-Klages, Sabine; Agace, William W.; Aghaeepour, Nima; Akdis, Mübeccel; Allez, Matthieu; Almeida, Larissa Nogueira; Alvisi, Giorgia; Anderson, Graham; Andrä, Immanuel; et al. (European Journal of Immunology, 2019)
These guidelines are a consensus work of a considerable number of members of the immunology and flow cytometry community. They provide the theory and key practical aspects of flow cytometry enabling immunologists to avoid the common errors that often undermine immunological data. Notably, there are comprehensive sections of all major immune cell types with helpful Tables detailing phenotypes in murine and human cells. The latest flow cytometry techniques and applications are also described, featuring examples of the data that can be generated and, importantly, how the data can be analysed. Furthermore, there are sections detailing tips, tricks and pitfalls to avoid, all written and peer-reviewed by leading experts in the field, making this an essential research companion.
CRIS-Team Scopus Importer:2019-10-29

Histological correlates of hippocampal magnetization transfer images in drug-resistant temporal lobe epilepsy patients - Peixoto-Santos, Jose Eduardo; Velasco, Tonicarlo R.; Carlotti, Carlos Gilberto; Assirati, Joao Alberto; Rezende, Gustavo Henrique de Souza e.; Kobow, Katja; Coras, Roland; Blümcke, Ingmar; Salmon, Carlos Ernesto Garrido; Santos, Antonio Carlos dos; Leite, Joao Pereira (NeuroImage: Clinical, 2020)
Objective: Temporal lobe epilepsy patients (TLE) often present with hippocampal atrophy, increased T2 relaxation, and reduced magnetization transfer ratio (MTR) in magnetic resonance images (MRI). The histological correlates of the reduced hippocampal MTR are so far unknown. Since MTR is dependent on the tissue's macromolecules, our aim was to evaluate the correlations between cellular populations, extracellular matrix molecules and the MTR in TLE patients. Methods: Patients with TLE (n = 26) and voluntaries (=20) were scanned in a 3 Tesla MRI scanner, and MTR images were calculated from 3DT1 sequences with magnetization pulse on resonance. Immunohistochemistry for neurons, reactive astrocytes, activated microglia, and extracellular matrix chondroitin sulfate were performed in formalin fixed, paraffin embedded tissues of TLE and autopsy controls (n = 10). Results were considered significant with adjusted p < 0.05. Results: Compared to the respective controls, TLE patients had reduced hippocampal MTR, increased reactive astrocytes and activated microglia, increased extracellular chondroitin sulfate, and reduced neuron density, compares to controls. MTR correlated positively with neuron density in CA3 and with chondroitin sulfate in CA3 and CA1. Multiple linear regressions reinforced the correlations between chondroitin sulfate and MTR. Significance: Our data indicate that extracellular matrix molecules are the most significant histological correlates of magnetization transfer ratio in the hippocampus of TLE patients.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Extracellular matrix; Hippocampal sclerosis; Magnetization transfer ratio; Neuron density; Temporal lobe epilepsy

Histopathological Findings in Brain Tissue Obtained during Epilepsy Surgery - Blümcke, Ingmar; Spreafico, R.; Haaker, G.; Coras, R.; Kobow, K.; Bien, C. G.; Pfaefflin, M.; Elger, C.; Widman, G.; Schramm, J.; Becker, Albert; Braun, K. P.; et al. (New England Journal of Medicine, 2017)
Detailed neuropathological information on the structural brain lesions underlying seizures is valuable for understanding drug-resistant focal epilepsy.We report the diagnoses made on the basis of resected brain specimens from 9523 patients who underwent epilepsy surgery for drug-resistant seizures in 36 centers from 12 European countries over 25 years. Histopathological diagnoses were determined through examination of the specimens in local hospitals (41%) or at the German Neuropathology Reference Center for Epilepsy Surgery (59%).The onset of seizures occurred before 18 years of age in 75.9% of patients overall, and 72.5% of the patients underwent surgery as adults. The mean duration of epilepsy before surgical resection was 20.1 years among adults and 5.3 years among children. The temporal lobe was involved in 71.9% of operations. There were 36 histopathological diagnoses in seven major disease categories. The most common categories were hippocampal sclerosis, found in 36.4% of the patients (88.7% of cases were in adults), tumors (mainly ganglioglioma) in 23.6%, and malformations of cortical development in 19.8% (focal cortical dysplasia was the most common type, 52.7% of cases of which were in children). No histopathological diagnosis could be established for 7.7% of the patients.In patients with drug-resistant focal epilepsy requiring surgery, hippocampal sclerosis was the most common histopathological diagnosis among adults, and focal cortical dysplasia was the most common diagnosis among children. Tumors were the second most common lesion in both groups. (Funded by the European Union and others.).
EVALuna2:7385

Human brain tissue with MOGHE carrying somatic SLC35A2 variants reveal aberrant protein expression and protein loss in the white matter - Cecchini, Erica; Geffers, Simon; Coras, Roland; Schultheis, Dorothea; Holtzhausen, Christian; Karandasheva, Kristina; Herrmann, Harald; Paulsen, Friedrich; Stadelmann, Christine; Kobow, Katja; Hartlieb, Till; Bien, Christian; et al. (Acta Neuropathologica, 2025)
Mild Malformation of Cortical Development with Oligodendroglial Hyperplasia in Epilepsy (MOGHE) is a recently described disease entity primarily affecting young children with drug-resistant epilepsy, mainly affecting the frontal lobe. The condition is histopathologically defined by focal lesions with patchy areas of increased oligodendroglial cell density at the grey-white matter boundary and heterotopic neurons in the white matter. Approximately half of the individuals with MOGHE carry brain somatic variants in the SLC35A2 gene, which affects the UDP-galactose transporter and thus sphingolipid glycosylation. To investigate the impact of SLC35A2 variants on protein expression, we analysed MOGHE brain tissue with and without SLC35A2 mosaicism, distinguishing missense from nonsense variants. We developed an antibody targeting the N-terminus of the SLC35A2 galactose transporter and applied it for immunofluorescence (IF) analyses in a MOGHE cohort comprising 59 genetically tested individuals selected from three centres in Germany. The cohort included 13 individuals with SLC35A2 missense variants and 15 with SLC35A2 nonsense variants. Our findings confirm the localisation of the SLC35A2 protein in the Golgi apparatus of all neuroepithelial cell types as well as within Golgi outposts along oligodendroglial processes. The protein distribution was altered in MOGHE samples dependent on the SLC35A2 variant and its allelic frequency. Western blot and IF analyses revealed a significant SLC35A2 reduction in MOGHE tissues carrying nonsense variants. Ultrastructural analyses from three MOGHE samples demonstrated hypomyelination in regions with increased oligodendroglial cell densities, regardless of the harbouring of SLC35A2 variants. Notably, this hypomyelination pattern decreased with age. These results suggested a role for the SLC35A2 protein in the pathogenesis of MOGHE and indicated the presence of additional myelin-associated pathomechanisms in those individuals who do not carry a pathogenic SLC35A2 varian
CRIS-Team Scopus Importer:2025-03-21
Keywords: MOGHE; Neuropathology; Brain; Myelin; Oligodendrocytes; Epilepsy

Low-grade epilepsy-associated neuroepithelial tumours - the 2016 WHO classification - Blümcke, Ingmar; Aronica, Eleonord; Becker, Albert; Capper, David; Coras, Roland; Honavar, Mrinalini; Jacques, Thomas S.; Kobow, Katja; Miyata, Hajime; Muhlebner, Angelika; Pimentel, Jose; Soylemezoglu, Figen; et al. (Nature Reviews Neurology, 2016)
Rapid developments in molecular genetic technology and research have swiftly advanced our understanding of neuro-oncology. As a consequence, the WHO invited their expert panels to revise the current classification system of brain tumours and to introduce, for the first time, a molecular genetic approach for selected tumour entities, thus setting a new gold standard in histopathology. The revised 5th edition of the 'blue book' was released in May 2016 and will have a major impact in stratifying diagnosis and treatment. However, low-grade neuroepithelial tumours that present with early-onset focal epilepsy and are mostly seen in children and young adults (previously designated as long-term epilepsy-associated neuroepithelial tumours, LEAT) lack such innovative clinicopathological and molecular genetic tools. The Neuropathology Task Force of the International League against Epilepsy will critically discuss this issue, and will offer perspectives on how to decipher and validate clinically meaningful LEAT entities using the current WHO approach that integrates clinicopathological and genetic classification systems.
EVALuna2:7352

Low proliferation and differentiation capacities of adult hippocampal stem cells correlate with memory dysfunction in humans - Coras, Roland; Siebzehnrübl, Florian; Pauli, Elisabeth; Huttner, Hagen; Njunting, Marleisje; Kobow, Katja; Villmann, Carmen; Hahnen, Eric; Neuhuber, Winfried; Weigel, Daniel; Buchfelder, Michael; Stefan, Herrmann; et al. (Brain, 2010)
The hippocampal dentate gyrus maintains its capacity to generate new neurons throughout life. In animal models, hippocampal neurogenesis is increased by cognitive tasks, and experimental ablation of neurogenesis disrupts specific modalities of learning and memory. In humans, the impact of neurogenesis on cognition remains unclear. Here, we assessed the neurogenic potential in the human hippocampal dentate gyrus by isolating adult human neural stem cells from 23 surgical en bloc hippocampus resections. After proliferation of the progenitor cell pool in vitro we identified two distinct patterns. Adult human neural stem cells with a high proliferation capacity were obtained in 11 patients. Most of the cells in the high proliferation capacity cultures were capable of neuronal differentiation (53 +/- 13% of in vitro cell population). A low proliferation capacity was observed in 12 specimens, and only few cells differentiated into neurons (4 +/- 2%). This was reflected by reduced numbers of proliferating cells in vivo as well as granule cells immunoreactive for doublecortin, brain-derived neurotrophic factor and cyclin-dependent kinase 5 in the low proliferation capacity group. High and low proliferation capacity groups differed dramatically in declarative memory tasks. Patients with high proliferation capacity stem cells had a normal memory performance prior to epilepsy surgery, while patients with low proliferation capacity stem cells showed severe learning and memory impairment. Histopathological examination revealed a highly significant correlation between granule cell loss in the dentate gyrus and the same patient's regenerative capacity in vitro (r = 0.813; P < 0.001; linear regression: R-adjusted(2) = 0.635), as well as the same patient's ability to store and recall new memories (r = 0.966; P = 0.001; linear regression: R-adjusted(2) = 0.9). Our results suggest that encoding new memories is related to the regenerative capacity of the hippocampus in the human brain.
Keywords: stem cells; neurogenesis; hippocampus; memory; learning; epilepsy; doublecortin

Molecular diagnostics in drug-resistant focal epilepsy define new disease entities. - Kobow, Katja; Baulac, Stéphanie; von Deimling, Andreas; Lee, Jeong Ho (Brain Pathology, 2021)
Structural brain lesions, including the broad range of malformations of cortical development (MCD) and glioneuronal tumors, are among the most common causes of drug-resistant focal epilepsy. Epilepsy surgery can provide a curative treatment option in respective patients. The currently available pre-surgical multi-modal diagnostic armamentarium includes high- and ultra-high resolution magnetic resonance imaging (MRI) and intracerebral EEG to identify a focal structural brain lesion as epilepsy underlying etiology. However, specificity and accuracy in diagnosing the type of lesion have proven to be limited. Moreover, the diagnostic process does not stop with the decision for surgery. The neuropathological diagnosis remains the gold standard for disease classification and patient stratification, but is particularly complex with high inter-observer variability. Here, the identification of lesion-specific mosaic variants together with epigenetic profiling of lesional brain tissue became new tools to more reliably identify disease entities. In this review, we will discuss how the paradigm shifts from histopathology toward an integrated diagnostic approach in cancer and the more recent development of the DNA methylation-based brain tumor classifier have started to influence epilepsy diagnostics. Some examples will be highlighted showing how the diagnosis and our mechanistic understanding of difficult to classify structural brain lesions associated with focal epilepsy has improved with molecular genetic data being considered in decision making.

Mosaic trisomy of chromosome 1q in human brain tissue associates with unilateral polymicrogyria, very early-onset focal epilepsy, and severe developmental delay - Kobow, Katja; Jabari, Samir; Pieper, Tom; Kudernatsch, Manfred; Polster, Tilman; Woermann, Friedrich G.; Kalbhenn, Thilo; Hamer, Hajo; Roessler, Karl; Muhlebner, Angelika; Spliet, Wim G. M.; Feucht, Martha; et al. (Acta Neuropathologica, 2020)
Polymicrogyria (PMG) is a developmental cortical malformation characterized by an excess of small and frustrane gyration and abnormal cortical lamination. PMG frequently associates with seizures. The molecular pathomechanisms underlying PMG development are not yet understood. About 40 genes have been associated with PMG, and small copy number variations have also been described in selected patients. We recently provided evidence that epilepsy-associated structural brain lesions can be classified based on genomic DNA methylation patterns. Here, we analyzed 26 PMG patients employing array-based DNA methylation profiling on formalin-fixed paraffin-embedded material. A series of 62 well-characterized non-PMG cortical malformations (focal cortical dysplasia type 2a/b and hemimegalencephaly), temporal lobe epilepsy, and non-epilepsy autopsy controls was used as reference cohort. Unsupervised dimensionality reduction and hierarchical cluster analysis of DNA methylation profiles showed that PMG formed a distinct DNA methylation class. Copy number profiling from DNA methylation data identified a uniform duplication spanning the entire long arm of chromosome 1 in 7 out of 26 PMG patients, which was verified by additional fluorescence in situ hybridization analysis. In respective cases, about 50% of nuclei in the center of the PMG lesion were 1q triploid. No chromosomal imbalance was seen in adjacent, architecturally normal-appearing tissue indicating mosaicism. Clinically, PMG 1q patients presented with a unilateral frontal or hemispheric PMG without hemimegalencephaly, a severe form of intractable epilepsy with seizure onset in the first months of life, and severe developmental delay. Our results show that PMG can be classified among other structural brain lesions according to their DNA methylation profile. One subset of PMG with distinct clinical features exhibits a duplication of chromosomal arm 1q.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Brain development; Chromosome 1; Copy number variation; Cortical malformation; ID; Seizures

Multilobar unilateral hypoplasia with emphasis on the posterior quadrant and severe epilepsy in children with FCD ILAE Type 1A - Holthausen, Hans; Coras, Roland; Tang, Yingying; Bai, Lily; Wang, Irene; Pieper, Tom; Kudernatsch, Manfred; Hartlieb, Till; Staudt, Martin; Winkler, Peter; Hofer, Wiebke; Jabari, Samir; et al. (Epilepsia, 2021)
Objective: Focal cortical dysplasia (FCD) Type 1 and its three subtypes have yet not been fully characterized at the clinical, anatomopathological, and molecular level (International League Against Epilepsy [ILAE] FCD classification from 2011). We aimed to describe the clinical phenotype of patients with histopathologically confirmed FCD1A obtained from a single epilepsy center between 2002 and 2016. Methods: Medical records were retrieved from the hospital's archive. Results from electroencephalography (EEG) video recordings, neuroimaging, and histopathology were reevaluated. Magnetic resonance imaging (MRI) post-processing was retrospectively performed in nine patients. DNA methylation studies were carried out from archival surgical brain tissue in 11 patients. Results: Nineteen children with a histopathological diagnosis of FCD1A were included. The average onset of epilepsy was 0.9 years (range 0.2–10 years). All children had severe cognitive impairment and one third had mild motor deficits, yet fine finger movements were preserved in all patients. All patients had daily seizures, being drug resistant from disease onset. Interictal electroencephalography revealed bilateral multi-regional epileptiform discharges. Interictal status epilepticus was observed in 8 and countless subclinical seizures in 11 patients. Regional continuous irregular slow waves were of higher lateralizing and localizing yield than spikes. Posterior background rhythms were normal in 16 of 19 children. Neuroimaging showed unilateral multilobar hypoplasia and increased T2-FLAIR signals of the white matter in 18 of 19 patients. All children underwent tailored multilobar resections, with seizure freedom achieved in 47% (Engel class I). There was no case with frontal involvement without involvement of the posterior quadrant by MRI and histopathology. DNA methylation profiling distinguished FCD1A samples from all other epilepsy specimens and controls. Significance: We identified a cohort of young children with drug resistance from seizure onset, bad EEG with posterior emphasis, lack of any focal neurological deficits but severe cognitive impairment, subtle hypoplasia of the epileptogenic area on MRI, and histopathologically defined and molecularly confirmed by DNA methylation analysis as FCD ILAE Type 1A.
CRIS-Team Scopus Importer:2021-11-12
Keywords: brain; neuroimaging; neuropathology; neurophysiology; seizure

Neocortical development and epilepsy: insights from focal cortical dysplasia and brain tumours - Blümcke, Ingmar; Budday, Silvia; Poduri, Annapurna; Lal, Dennis; Kobow, Katja; Baulac, Stephanie (Lancet Neurology, 2021)
During the past decade, there have been considerable advances in understanding of the genetic and morphogenic processes underlying cortical malformations and developmental brain tumours. Focal malformations are caused by somatic (postzygotic) variants in genes related to cell growth (ie, in the mTOR pathway in focal cortical dysplasia type 2), which are acquired in neuronal progenitors during neurodevelopment. In comparison, developmental brain tumours result from somatic variants in genes related to cell proliferation (eg, in the MAP-kinase pathway in ganglioglioma), which affect proliferating glioneuronal precursors. The timing of the genetic event and the specific gene involved during neurodevelopment will drive the nature and size of the lesion, whether it is a developmental malformation or a brain tumour. There is also emerging evidence that epigenetic processes underlie a molecular memory in epileptogenesis. This knowledge will together facilitate understanding of why and how patients with these lesions have epilepsy, and could form a basis for a move towards precision medicine for this challenging cohort of patients.
CRIS-Team Scopus Importer:2021-10-29

Neuropathologic measurements in focal cortical dysplasias: validation of the ILAE 2011 classification system and diagnostic implications for MRI - Mühlebner, Angelika; Coras, Roland; Kobow, Katja; Feucht, Martha; Czech, Thomas; Stefan, Hermann; Buchfelder, Michael; Holthausen, Hans; Kudernatsch, Manfred; Blümcke, Ingmar; et al. (Acta Neuropathologica, 2012)
Focal cortical dysplasias (FCD) which represent a composite group of cortical malformations are increasingly recognized as morphological substrate for severe therapy-refractory epilepsy in children and young adults. However, presurgical evaluation remains challenging as not all FCD variants can be reliably detected by high-resolution magnetic resonance imaging (MRI). Here, we studied a cohort of 52 epilepsy patients with neuropathological evidence for FCD using the 2011 classification of the International League against Epilepsy (ILAE) and systematically analysed those histopathologic features applicable also for MRI diagnostics. Histopathologic parameters included quantitative measurements of cellular profiles, cortical thickness, heterotopic neurons in white matter, and myelination that were compared between FCD subtypes and age-/localization-matched controls (n = 36) using multivariate analysis. Dysmorphic neurons in both FCD Type II variants showed significantly increased diameter of their cell bodies and nuclei. Cortical thickness was also increased with a distinct loss of myelin content specifying FCD Type IIb from IIa. The data further suggested that myelination deficits in FCD Type IIb result from compromised oligodendroglial lineage differentiation and we concluded that the "transmantle sign" is a unique finding in FCD Type IIb. In contrast, FCD Type Ia was characterized by a smaller cortical ribbon and higher neuronal densities, but these parameters failed to reach statistical significance (considering age-and location-dependent variability in controls). All FCD variants showed abnormal grey-white matter boundaries with increased numbers of heterotopic neurons. Similar results were obtained also at deep white matter location. Thus, many FCD variants may indeed escape visual MRI inspection, but suspicious areas with increased or decreased cortical thickness as well as grey-white matter blurring may be uncovered using post-processing protocols of neuroimaging data. The systematic analysis of well-specified histopathological features could be helpful to improve sensitivity and specificity in MRI detection during pre-surgical work-up of patients with drug-resistant focal epilepsies.
Keywords: Malformations; Neocortex; MRI; Seizures; Epilepsy; Neuropathology

No evidence for human papillomavirus infection in focal cortical dysplasia IIb - Coras, Roland; Korn, Klaus; Bien, Christian G.; Kalbhenn, Thilo; Roessler, Karl; Kobow, Katja; Giedl, Josef; Fleckenstein, Bernhard; Blümcke, Ingmar (Annals of Neurology, 2015)
The etiology of focal cortical dysplasia type IIb (FCDIIb) remains enigmatic in patients suffering from drug-resistant epilepsy, and an aberrant activation of the mammalian target of rapamycin complex 1 signaling pathway (mTORC1) was detected in this developmental brain malformation. Recently, the human papillomavirus (HPV) oncoprotein E6 has been identified as a potent activator of mTORC1, and HPV16 E6 has been described to persist in balloon cells obtained from surgical FCDIIb specimens. Although this observation was replicated by an independent second report, it contradicts current knowledge of HPV biology. HPV infects the squamous or mucocutaneous epithelium; hematogenic spread into other tissues has not been observed. In addition, brain carcinogenesis has never been reported in FCDIIb patients. Herein, we have tried to confirm 2 previous reports of HPV16 E6 infection using an independent series of 14 surgical specimens with histopathologically confirmed FCDIIb.Snap-frozen FCDIIb specimens were tested for HPV DNA using the primer set for amplification of the complete E6 reading frame of HPV16 and 3 other sets of primers (2 consensus primer sets detecting multiple HPV genotypes, and another primer set specifically used for HPV16). Furthermore, formalin-fixed and paraffin-embedded histopathological preparations were immunohistochemically analyzed using previously described antibodies directed against the HPV E6 oncoprotein.All 14 FCDIIb specimens were negative for HPV DNA with all 4 primer sets. Antibodies directed against the HPV E6 epitope showed weak labeling of cytoplasm in balloon cells, as previously described in FCDIIb, but also in other cell populations.Our data did not confirm previously reported evidence for HPV16 detection in FCDIIb. Ann Neurol 2015;77:312-319.
EVALuna2:6690

Ontology-based feature engineering in machine learning workflows for heterogeneous epilepsy patient records - Sahoo, Satya S.; Kobow, Katja; Zhang, Jianzhe; Buchhalter, Jeffrey; Dayyani, Mojtaba; Upadhyaya, Dipak P.; Prantzalos, Katrina; Bhattacharjee, Meenakshi; Blümcke, Ingmar; Wiebe, Samuel; Lhatoo, Samden D. (Scientific Reports, 2022)
Biomedical ontologies are widely used to harmonize heterogeneous data and integrate large volumes of clinical data from multiple sources. This study analyzed the utility of ontologies beyond their traditional roles, that is, in addressing a challenging and currently underserved field of feature engineering in machine learning workflows. Machine learning workflows are being increasingly used to analyze medical records with heterogeneous phenotypic, genotypic, and related medical terms to improve patient care. We performed a retrospective study using neuropathology reports from the German Neuropathology Reference Center for Epilepsy Surgery at Erlangen, Germany. This cohort included 312 patients who underwent epilepsy surgery and were labeled with one or more diagnoses, including dual pathology, hippocampal sclerosis, malformation of cortical dysplasia, tumor, encephalitis, and gliosis. We modeled the diagnosis terms together with their microscopy, immunohistochemistry, anatomy, etiologies, and imaging findings using the description logic-based Web Ontology Language (OWL) in the Epilepsy and Seizure Ontology (EpSO). Three tree-based machine learning models were used to classify the neuropathology reports into one or more diagnosis classes with and without ontology-based feature engineering. We used five-fold cross validation to avoid overfitting with a fixed number of repetitions while leaving out one subset of data for testing, and we used recall, balanced accuracy, and hamming loss as performance metrics for the multi-label classification task. The epilepsy ontology-based feature engineering approach improved the performance of all the three learning models with an improvement of 35.7%, 54.5%, and 33.3% in logistics regression, random forest, and gradient tree boosting models respectively. The run time performance of all three models improved significantly with ontology-based feature engineering with gradient tree boosting model showing a 93.8% reduction in the time required for training and testing of the model. Although, all three models showed an overall improved performance across the three-performance metrics using ontology-based feature engineering, the rate of improvement was not consistent across all input features. To analyze this variation in performance, we computed feature importance scores and found that microscopy had the highest importance score across the three models, followed by imaging, immunohistochemistry, and anatomy in a decreasing order of importance scores. This study showed that ontologies have an important role in feature engineering to make heterogeneous clinical data accessible to machine learning models and also improve the performance of machine learning models in multilabel multiclass classification tasks.
Created from Fastlane, Scopus look-up

Same same but different: A Web-based deep learning application revealed classifying features for the histopathologic distinction of cortical malformations - Kubach, Joshua; Muhlebner-Fahrngruber, Angelika; Soylemezoglu, Figen; Miyata, Hajime; Niehusmann, Pitt; Honavar, Mrinalini; Rogerio, Fabio; Kim, Se-Hoon; Aronica, Eleonora; Garbelli, Rita; Vilz, Samuel; Popp, Alexander; et al. (Epilepsia, 2020)
Objective: The microscopic review of hematoxylin-eosin–stained images of focal cortical dysplasia type IIb and cortical tuber of tuberous sclerosis complex remains challenging. Both entities are distinct subtypes of human malformations of cortical development that share histopathological features consisting of neuronal dyslamination with dysmorphic neurons and balloon cells. We trained a convolutional neural network (CNN) to classify both entities and visualize the results. Additionally, we propose a new Web-based deep learning application as proof of concept of how deep learning could enter the pathologic routine. Methods: A digital processing pipeline was developed for a series of 56 cases of focal cortical dysplasia type IIb and cortical tuber of tuberous sclerosis complex to obtain 4000 regions of interest and 200 000 subsamples with different zoom and rotation angles to train a neural network. Guided gradient-weighted class activation maps (Guided Grad-CAMs) were generated to visualize morphological features used by the CNN to distinguish both entities. Results: Our best-performing network achieved 91% accuracy and 0.88 area under the receiver operating characteristic curve at the tile level for an unseen test set. Novel histopathologic patterns were found through the visualized Guided Grad-CAMs. These patterns were assembled into a classification score to augment decision-making in routine histopathology workup. This score was successfully validated by 11 expert neuropathologists and 12 nonexperts, boosting nonexperts to expert level performance. Significance: Our newly developed Web application combines the visualization of whole slide images with the possibility of deep learning–aided classification between focal cortical dysplasia IIb and tuberous sclerosis complex. This approach will help to introduce deep learning applications and visualization for the histopathologic diagnosis of rare and difficult-to-classify brain lesions.
CRIS-Team Scopus Importer:2020-03-06
Keywords: brain; convolutional neural network; cortical malformations; deep learning; digital pathology; epilepsy

Small leucine-rich proteoglycans inhibit CNS regeneration by modifying the structural and mechanical properties of the lesion environment - Kolb, Julia; Tsata, Vasiliki; John, Nora; Kim, Kyoohyun; Möckel, Conrad; Rosso, Gonzalo; Kurbel, Veronika; Parmar, Asha; Sharma, Gargi; Karandasheva, Kristina; Abuhattum, Shada; Lyraki, Olga; et al. (Nature Communications, 2023)
Extracellular matrix (ECM) deposition after central nervous system (CNS) injury leads to inhibitory scarring in humans and other mammals, whereas it facilitates axon regeneration in the zebrafish. However, the molecular basis of these different fates is not understood. Here, we identify small leucine-rich proteoglycans (SLRPs) as a contributing factor to regeneration failure in mammals. We demonstrate that the SLRPs chondroadherin, fibromodulin, lumican, and prolargin are enriched in rodent and human but not zebrafish CNS lesions. Targeting SLRPs to the zebrafish injury ECM inhibits axon regeneration and functional recovery. Mechanistically, we find that SLRPs confer mechano-structural properties to the lesion environment that are adverse to axon growth. Our study reveals SLRPs as inhibitory ECM factors that impair axon regeneration by modifying tissue mechanics and structure, and identifies their enrichment as a feature of human brain and spinal cord lesions. These findings imply that SLRPs may be targets for therapeutic strategies to promote CNS regeneration.<br
Keywords: Biophysics; Mechanisms of disease; Spinal cord injury

The emerging role of DNA methylation in epileptogenesis - Kobow, Katja; Blümcke, Ingmar (Epilepsia, 2012)
DNA methylation is a covalent chromatin modification, characterized by the biochemical addition of a methyl group (-CH3) to cytosine nucleotides via a DNA methyltransferase enzyme. 5'-Methylcytosine (5-mC), frequently called the fifth base, has been implicated in genome stability, silencing of transposable elements, and repression of gene expression. Through the latter, DNA methylation dynamics broadly influence brain development, function, and aging. Aberrant DNA methylation patterns, either localized to specific gene regions or scattered throughout the genome, are associated with many neurologic disorders. Herein, we discuss the emerging role of DNA methylation in epileptogenesis and the perspectives arising from epigenetic medicine as new therapeutic strategy in difficult-to-treat epilepsies.
Keywords: Brain; Epilepsy; Seizures; Epigenetics; Transmethylation; Epigenetic medicine

The genomic landscape across 474 surgically accessible epileptogenic human brain lesions - A López-Rivera, Javier; Leu, Costin; Macnee, Marie; Khoury, Jean; Hoffmann, Lucas; Coras, Roland; Kobow, Katja; Bhattarai, Nisha; Pérez-Palma, Eduardo; Hamer, Hajo; Brandner, Sebastian; Rössler, Karl; et al. (Brain, 2022)
Understanding the exact molecular mechanisms involved in the etiology of epileptogenic pathologies with or without tumor activity is essential for improving treatment of drug-resistant focal epilepsy. Here, we characterize the landscape of somatic genetic variants in resected brain specimens from 474 individuals with drug-resistant focal epilepsy using deep whole-exome sequencing (>350×) and whole-genome genotyping. Across the exome, we observe a greater number of somatic single-nucleotide variants (SNV) in low-grade epilepsy-associated tumors (LEAT; 7.92 ± 5.65 SNV) than in brain tissue from malformations of cortical development (MCD; 6.11 ± 4 SNV) or hippocampal sclerosis (HS; 5.1 ± 3.04 SNV). Tumor tissues also had the largest number of likely pathogenic variant carrying cells. LEAT had the highest proportion of samples with one or more somatic copy number variants (CNV; 24.7%), followed by MCD (5.4%) and HS (4.1%). Recurring somatic whole chromosome duplications affecting Chromosome 7 (16.8%), chromosome 5 (10.9%), and chromosome 20 (9.9%) were observed among LEAT. For germline variant-associated MCD genes such as TSC2, DEPDC5, and PTEN, germline SNV were frequently identified within large loss of heterozygosity regions, supporting the recently proposed ‘second hit’ disease mechanism in these genes. We detect somatic variants in twelve established lesional epilepsy genes and demonstrate exome-wide statistical support for three of these in the etiology of LEAT (e.g., BRAF) and MCD (e.g., SLC35A2 and MTOR). We also identify novel significant associations for PTPN11 with LEAT and NRAS Q61 mutated protein with a complex MCD characterized by polymicrogyria and nodular heterotopia. The variants identified in NRAS are known from cancer studies to lead to hyperactivation of NRAS, which can be targeted pharmacologically. We identify large recurrent 1q21-q44 duplication including AKT3 in association with focal cortical dysplasia type 2a with hyaline astrocytic inclusions, another rare and possibly under-recognized brain lesion. The clinical genetic analyses showed that the numbers of somatic SNV across the exome and the fraction of affected cells were positively correlated with the age at seizure onset and surgery in individuals with LEAT. In summary, our comprehensive genetic screen sheds light on the genome-scale landscape of genetic variants in epileptic brain lesions, informs the design of gene panels for clinical diagnostic screening, and guides future directions for clinical implementation of epilepsy surgery genetics.<br
Keywords: epilepsy; malformation of cortical development; low-grade epilepsy-associated tumor; hippocampal sclerosis; genetics

The ILAE classification of focal cortical dysplasia in clinical routine Die ILAE-Klassifikation fokaler kortikaler Dysplasien im klinischen Gebrauch - Blümcke, Ingmar; Kobow, Katja; Holthausen, Hans (Zeitschrift für Epileptologie, 2017)
We would like to discuss the benefits as well as ongoing challenges of the International League Against Epilepsy (ILAE) first consensus classification of focal cortical dysplasia (FCD) published in 2011. FCD is a frequent cause of early onset and drug-resistant focal epilepsy. Success of neurosurgical therapy, however, largely depends on the clinico-pathological subtype, which has been classified into three major subtypes: FCD type 1 is a rare disease frequently observed in young children and is a radiologically, electroclinically and histopathologically difficult to diagnose epilepsy. Post-surgical seizure control is less successful compared to FCD type 2A or FCD type 2B. These FCD type 2 variants are radiologically, electroclinically and histopathologically well described and probably share molecular mutations with other mTORopathies, such as hemimegalencephaly and tuberous sclerosis complex. FCD type 3 is associated with other principal lesions, such as hippocampal sclerosis (FCD 3A), epilepsy-associated tumors (FCD 3B), vascular malformations (FCD 3C) and other lesions acquired during early life (FCD 3D). The pathomechanism remains to be elucidated and success of surgical therapy is often similar to that of the principal lesions rather than being a distinct feature. An up-coming revision of the ILAE classification is currently under discussion to cover progress in molecular diagnostics (as shown in other medical disciplines, please refer to the tumor chapter of this issue); however, major changes in the three-tiered classification scheme are not expected.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Brain; Cortex; Dysplasia; Neuropathology; Seizure

The ILAE consensus classification of focal cortical dysplasia: An update proposed by an ad hoc task force of the ILAE diagnostic methods commission - Najm, Imad; Lal, Dennis; Alonso Vanegas, Mario; Cendes, Fernando; Lopes-Cendes, Iscia; Palmini, Andre; Paglioli, Eliseu; Sarnat, Harvey B.; Walsh, Christopher A.; Wiebe, Samuel; Aronica, Eleonora; Baulac, Stephanie; et al. (Epilepsia, 2022)
Ongoing challenges in diagnosing focal cortical dysplasia (FCD) mandate continuous research and consensus agreement to improve disease definition and classification. An International League Against Epilepsy (ILAE) Task Force (TF) reviewed the FCD classification of 2011 to identify existing gaps and provide a timely update. The following methodology was applied to achieve this goal: a survey of published literature indexed with ((Focal Cortical Dysplasia) AND (epilepsy)) between 01/01/2012 and 06/30/2021 (n = 1349) in PubMed identified the knowledge gained since 2012 and new developments in the field. An online survey consulted the ILAE community about the current use of the FCD classification scheme with 367 people answering. The TF performed an iterative clinico-pathological and genetic agreement study to objectively measure the diagnostic gap in blood/brain samples from 22 patients suspicious for FCD and submitted to epilepsy surgery. The literature confirmed new molecular-genetic characterizations involving the mechanistic Target Of Rapamycin (mTOR) pathway in FCD type II (FCDII), and SLC35A2 in mild malformations of cortical development (mMCDs) with oligodendroglial hyperplasia (MOGHE). The electro-clinical-imaging phenotypes and surgical outcomes were better defined and validated for FCDII. Little new information was acquired on clinical, histopathological, or genetic characteristics of FCD type I (FCDI) and FCD type III (FCDIII). The survey identified mMCDs, FCDI, and genetic characterization as fields for improvement in an updated classification. Our iterative clinico-pathological and genetic agreement study confirmed the importance of immunohistochemical staining, neuroimaging, and genetic tests to improve the diagnostic yield. The TF proposes to include mMCDs, MOGHE, and “no definite FCD on histopathology” as new categories in the updated FCD classification. The histopathological classification can be further augmented by advanced neuroimaging and genetic studies to comprehensively diagnose FCD subtypes; these different levels should then be integrated into a multi-layered diagnostic scheme. This update may help to foster multidisciplinary efforts toward a better understanding of FCD and the development of novel targeted treatment options.
CRIS-Team Scopus Importer:2022-06-24
Keywords: brain; classification; epilepsy; focal cortical dysplasia; genes; seizure

The methylation hypothesis: Do epigenetic chromatin modifications play a role in epileptogenesis? - Kobow, Katja; Blümcke, Ingmar (Epilepsia, 2011)
Any structural brain lesion can provoke epilepsy, although onset and progression of seizures as well as response to antiepileptic drug (AED) treatment remain difficult to predict in each patient. Tremendous work has focused on the development of new AED compounds with the intention to treat seizures. However, these efforts have not yet discovered a "magic bullet" that cures epilepsy in every patient or modifies disease progression. With the "methylation hypothesis" we propose that epigenetic mechanisms play a pivotal role in epileptogenesis in patients with structural lesions. "Epigenetics" is defined as information that is heritable during cell division other than the DNA sequence itself, that is, DNA methylation or histone tail modifications, which can produce lasting alterations in chromatin structure and gene expression. They are increasingly recognized as fundamental regulatory processes in central nervous system development, synaptic plasticity, and memory, and also play a role in neurologic disorders such as schizophrenia and spinal muscular atrophy. The methylation hypothesis suggests that seizures by themselves can induce epigenetic chromatin modifications, thereby aggravating the epileptogenic condition. The impact of the methylation hypothesis for new-onset epilepsy will be discussed. Unravelling of epigenetic pathomechanisms will also open new strategies to identify molecular targets for pharmacologic treatment in epilepsies.
Keywords: Epilepsy; DNA methylation; Histone modification; Epigenetic medicine

The methylation hypothesis of pharmacoresistance in epilepsy - Kobow, Katja; El-Osta, Assam; Blümcke, Ingmar (Epilepsia, 2013)
Seizures cannot be medically controlled in approximately 40% of people with epilepsy. Although we are beginning to understand how to better treat certain seizure types, we still do not know the regulatory events that determine antiepileptic drug resistance. Proposed pathoetiologic mechanisms include altered expression of drug targets (i.e., receptor or ion channel modifications), endothelial drug transporter activation (i.e., increasing drug clearance), or intrinsic severity factors. The latter hypothesis results from an often confirmed clinical observation, that seizure severity is a reliable predictor for the development of pharmacoresistance (PR) in epilepsy. Herein, we propose, that genome modifications that do not involve changes to the DNA sequence per se (i.e., epigenetic changes) could confer PR in patients with epilepsy. Seizures cause excessive neuronal membrane depolarization, which can influence the cellular nucleus; we thus hypothesize that seizures can mediate epigenetic modifications that result in persistent genomic methylation, histone density, and posttranslational modifications, as well as noncoding RNA-based changes. Although experimental evidence is lacking in epilepsy, such mechanisms are well characterized in cancer, either as a result of anticancer drugs themselves or cancer-related intrinsic signals (i.e., noncoding RNAs). We suggest that similar mechanisms also play a role in PR epilepsies. Addressing such epigenetic mechanisms may be a successful strategy to increase the brain's sensitivity to antiepileptic drugs and may even act as disease-modifying treatment.
EVALuna2:7221

The specific DNA methylation landscape in focal cortical dysplasia ILAE type 3D - Wang, Dan-Dan; Katoch, Mitali; Jabari, Samir; Blümcke, Ingmar; Blumenthal, David B.; Lu, De-Hong; Coras, Roland; Wang, Yu-Jiao; Shi, Jie; Zhou, Wen-Jing; Kobow, Katja; Piao, Yue-Shan (Acta Neuropathologica Communications, 2023)
Focal Cortical Dysplasia (FCD) is a frequent cause of drug-resistant focal epilepsy in children and young adults. The international FCD classifications of 2011 and 2022 have identified several clinico-pathological subtypes, either occurring isolated, i.e., FCD ILAE Type 1 or 2, or in association with a principal cortical lesion, i.e., FCD Type 3. Here, we addressed the DNA methylation signature of a previously described new subtype of FCD 3D occurring in the occipital lobe of very young children and microscopically defined by neuronal cell loss in cortical layer 4. We studied the DNA methylation profile using 850 K BeadChip arrays in a retrospective cohort of 104 patients with FCD 1 A, 2 A, 2B, 3D, TLE without FCD, and 16 postmortem specimens without neurological disorders as controls, operated in China or Germany. DNA was extracted from formalin-fixed paraffin-embedded tissue blocks with microscopically confirmed lesions, and DNA methylation profiles were bioinformatically analyzed with a recently developed deep learning algorithm. Our results revealed a distinct position of FCD 3D in the DNA methylation map of common FCD subtypes, also different from non-FCD epilepsy surgery controls or non-epileptic postmortem controls. Within the FCD 3D cohort, the DNA methylation signature separated three histopathology subtypes, i.e., glial scarring around porencephalic cysts, loss of layer 4, and Rasmussen encephalitis. Differential methylation in FCD 3D with loss of layer 4 mapped explicitly to biological pathways related to neurodegeneration, biogenesis of the extracellular matrix (ECM) components, axon guidance, and regulation of the actin cytoskeleton. Our data suggest that DNA methylation signatures in cortical malformations are not only of diagnostic value but also phenotypically relevant, providing the molecular underpinnings of structural and histopathological features associated with epilepsy. Further studies will be necessary to confirm these results and clarify their functional relevance and epileptogenic potential in these difficult-to-treat children.
CRIS-Team Scopus Importer:2023-08-18
Keywords: Epigenetic; Epilepsy; Malformation of cortical development; Neuropathology; Occipital lobe

WONOEP 2022: Neurotechnology for the diagnosis of epilepsy - Wagstyl, Konrad; Kobow, Katja; Casillas-Espinosa, Pablo M.; Cole, Andrew J.; Jiménez-Jiménez, Diego; Nariai, Hiroki; Baulac, Stéphanie; O'Brien, Terence; Henshall, David C.; Akman, Ozlem; Sankar, Raman; Galanopoulou, Aristea S.; et al. (Epilepsia, 2024)
Epilepsy's myriad causes and clinical presentations ensure that accurate diagnoses and targeted treatments remain a challenge. Advanced neurotechnologies are needed to better characterize individual patients across multiple modalities and analytical techniques. At the XVIth Workshop on Neurobiology of Epilepsy: Early Onset Epilepsies: Neurobiology and Novel Therapeutic Strategies (WONOEP 2022), the session on “advanced tools” highlighted a range of approaches, from molecular phenotyping of genetic epilepsy models and resected tissue samples to imaging-guided localization of epileptogenic tissue for surgical resection of focal malformations. These tools integrate cutting edge research, clinical data acquisition, and advanced computational methods to leverage the rich information contained within increasingly large datasets. A number of common challenges and opportunities emerged, including the need for multidisciplinary collaboration, multimodal integration, potential ethical challenges, and the multistage path to clinical translation. Despite these challenges, advanced epilepsy neurotechnologies offer the potential to improve our understanding of the underlying causes of epilepsy and our capacity to provide patient-specific treatment.
CRIS-Team Scopus Importer:2024-06-14
Keywords: artificial intelligence; epigenomics; focal epilepsy; high-frequency oscillations; histopathological diagnosis; intracranial EEG; molecular phenotyping; MRI; multiomics integration

WONOEP appraisal: new genetic approaches to study epilepsy - Rossignol, Elsa; Kobow, Katja; Simonato, Michele; Loeb, Jeffrey A.; Grisar, Thierry; Gilby, Krista L.; Vinet, Jonathan; Kadam, Shilpa D.; Becker, Albert J. (Epilepsia, 2014)
New genetic investigation techniques, including next-generation sequencing, epigenetic profiling, cell lineage mapping, targeted genetic manipulation of specific neuronal cell types, stem cell reprogramming, and optogenetic manipulations within epileptic networks are progressively unraveling the mysteries of epileptogenesis and ictogenesis. These techniques have opened new avenues to discover the molecular basis of epileptogenesis and to study the physiologic effects of mutations in epilepsy-associated genes on a multilayer level, from cells to circuits. This manuscript reviews recently published applications of these new genetic technologies in the study of epilepsy, as well as work presented by the authors at the genetic session of the XII Workshop on the Neurobiology of Epilepsy (WONOEP 2013) in Quebec, Canada. Next-generation sequencing is providing investigators with an unbiased means to assess the molecular causes of sporadic forms of epilepsy and has revealed the complexity and genetic heterogeneity of sporadic epilepsy disorders. To assess the functional impact of mutations in these newly identified genes on specific neuronal cell types during brain development, new modeling strategies in animals, including conditional genetics in mice and in utero knock-down approaches, are enabling functional validation with exquisite cell-type and temporal specificity. In addition, optogenetics, using cell-type-specific Cre recombinase driver lines, is enabling investigators to dissect networks involved in epilepsy. In addition, genetically encoded cell-type labeling is providing new means to assess the role of the nonneuronal components of epileptic networks such as glial cells. Furthermore, beyond its role in revealing coding variants involved in epileptogenesis, next-generation sequencing can be used to assess the epigenetic modifications that lead to sustained network hyperexcitability in epilepsy, including methylation changes in gene promoters and noncoding ribonucleic acid (RNA) involved in modifying gene expression following seizures. In addition, genetically based bioluminescent reporters are providing new opportunities to assess neuronal activity and neurotransmitter levels both in vitro and in vivo in the context of epilepsy. Finally, genetically rederived neurons generated from patient induced pluripotent stem cells and genetically modified zebrafish have become high-throughput means to investigate disease mechanisms and potential new therapies. Genetics has changed the field of epilepsy research considerably, and is paving the way for better diagnosis and therapies for patients with epilepsy.
EVALuna2:7249

WONOEP APPRAISAL: The many facets of epilepsy networks - Scott, Rod C.; De La Prida, Liset Menendez; Mahoney, J. Matt; Kobow, Katja; Sankar, Raman; De Curtis, Marco (Epilepsia, 2018)
The brain is a complex system composed of networks of interacting elements, from genes to circuits, whose function (and dysfunction) is not derivable from the superposition of individual components. Epilepsy is frequently described as a network disease, but to date, there is no standardized framework within which network concepts applicable to all levels from genes to whole brain can be used to generate deeper insights into the pathogenesis of seizures or the associated morbidities. To address this shortcoming, the Neurobiology Commission of the International League Against Epilepsy dedicated a Workshop on Neurobiology of Epilepsy (XIV WONOEP 2017) with the aim of formalizing network concepts as they apply to epilepsy and to critically discuss whether and how such concepts could augment current research endeavors. Here, we review concepts and strategies derived by considering epilepsy as a disease of different network hierarchies that range from genes to clinical phenotypes. We propose that the concept of networks is important for understanding epilepsy and is critical for developing new study designs. These approaches could ultimately facilitate the development of novel diagnostic and therapeutic strategies.
EVALuna2:36568